Interação, sentido e visibilidade no futebol de várzea em São Paulo: sujeitos, comunidades, marcas e uma cidade em jogo - Pereira, Tatiana Rovina Castro (2012)
This dissertation aims at studying the systems of interaction, sense and visibility that constitute the floodplain soccer practice in São Paulo city. In order to do so, citizens, communities and the city are understood as texts (in the semiotic comprehension of the term) as well as subjects involved in the interactive dynamics of the narrative significant that this type of soccer practice constitutes, bringing meaning in itself. It is intended to comprehend the construction of new meanings of this type of sports practice in practical life, which is done by several citizens in São Paulo city, especially in suburbia areas. Taking this type of soccer practice as the object of this study, the following question is proposed: how do subjects and communities of São Paulo city interact, build sense, show and see themselves through this type of soccer practice? Which interactions, senses and visibilities are constituted? The hypothesis is that this practice presents for the subject, the pairs (other subjects and communities) and the city beyond (and within) the floodplain identities and values which move these citizens in the relation with the city. The study is based theoretically on the Discursive Semiotics of A. J. Greimas and followers (with special focus on the works of D.L.P. Barros e J.L. Fiorin), the Sociosemiotics of E. Landowski and the Plastic Semiotic approach of A.C. de Oliveira, based on J-M. Floch. The corpus comprehends a historical research of soccer (and the several types of soccer which were constituted in São Paulo city, including the floodplain soccer practice) and the experience with the object in action and relation from 2010 to 2012, in the following competitions: Kaiser Cup of Amateur Soccer and Peace Cup Dreher, as well as in the Palmeirinha do Paraisópolis floodplain soccer team. The conclusion is that these subjects express, through the floodplain soccer practice, the values that rule their existence, in their life narratives. By re-semanticizing the sport which is Brazilians favorite , these players, supporters and community dwellers interact, feel and constitute a living shared among equals, enjoying the same way of life in the city. The new media destinators capitalized in the floodplain soccer practice in São Paulo city, such as Kaiser and Dreher, produce changes in the dynamics of sense production